BCG revaccination boosts adaptive polyfunctional Th1/Th17 and innate effectors in IGRA(+) and IGRA(–) Indian adults - Rakshit, Srabanti (JCI Insight, 2019)
BACKGROUND: Bacille Calmette-Guérin (BCG) vaccine is protective against Tuberculosis (TB) in children, but its efficacy wanes with age. Consequently, determining if BCG revaccination augments anti-TB immunity in young adults in TB endemic regions is vital. METHODS: Two hundred healthy adults, BCG vaccinated at birth, were tested for their IFN-γ release assay (IGRA) status. Of these, 28 IGRA(+) and 30 IGRA(–) were BCG revaccinated, and 24 IGRA(+) and 23 IGRA(–) subjects served as unvaccinated controls. T and innate cell responses to mycobacterial antigens were analyzed by 14-color flow cytometry over 34 weeks. RESULTS: IFN-γ and/or IL-2 Ag85A- and BCG-specific CD4(+) and CD8(+) T cell responses were boosted by revacciantion at 4 and 34 weeks, respectively, and were > 2-fold higher in IGRA(+) compared with IGRA(–) vaccinees. Polyfunctional Ag85A, BCG, and mycobacterium tuberculosis (Mtb) latency Ag–specific (LTAg-specific) CD4(+) T cells expressing up to 8 cytokines were also significantly enhanced in both IGRA(+) and IGRA(–) vaccinees relative to unvaccinated controls, most markedly in IGRA(+) vaccinees. A focused analysis of Th17 responses revealed expansion of Ag85A-, BCG-, and LTAg-specific total IL-17A(+),IL-17F(+),IL-22(+), and IL-10(+) CD4(+) T cell effectors in both IGRA(+) and IGRA(–) subjects. Also, innate IFN-γ(+) NK/γδ/NKT cell responses were higher in both IGRA(+) and IGRA(–) vaccinees compared with controls. This is the first evidence to our knowledge that BCG revaccination significantly boosts antimycobacterial Th1/Th17 responses in IGRA(+) and IGRA(–) subjects. CONCLUSION: These data show that BCG revaccination is immunogenic in IGRA(–) and IGRA(+) subjects, implying that Mtb preinfection in IGRA(+) subjects does not impact immunogenicity. This has implications for public health and vaccine development strategies. FUNDING: This work was funded principally by DBT-NIH (BT/MB/Indo-US/HIPC/2013).